Organic residue analysis shows sub-regional patterns in the use of pottery by Northern European hunter–gatherers. Issue 4 (22nd April 2020) - Courel, Blandine; Robson, Harry K.; Lucquin, Alexandre; Dolbunova, Ekaterina; Oras, Ester; Adamczak, Kamil; Andersen, Søren H.; Astrup, Peter Moe; Charniauski, Maxim; Czekaj-Zastawny, Agnieszka; Ezepenko, Igor; Hartz, Sönke; et al.
Abstract : The introduction of pottery vessels to Europe has long been seen as closely linked with the spread of agriculture and pastoralism from the Near East. The adoption of pottery technology by hunter–gatherers in Northern and Eastern Europe does not fit this paradigm, and its role within these communities is so far unresolved. To investigate the motivations for hunter–gatherer pottery use, here, we present the systematic analysis of the contents of 528 early vessels from the Baltic Sea region, mostly dating to the late 6th–5th millennium cal BC, using molecular and isotopic characterization techniques. The results demonstrate clear sub-regional trends in the use of ceramics by hunter–gatherers; aquatic resources in the Eastern Baltic, non-ruminant animal fats in the Southeastern Baltic, and a more variable use, including ruminant animal products, in the Western Baltic, potentially including dairy. We found surprisingly little evidence for the use of ceramics for non-culinary activities, such as the production of resins. We attribute the emergence of these sub-regional cuisines to the diffusion of new culinary ideas afforded by the adoption of pottery, e.g. cooking and combining foods, but culturally contextualized and influenced by traditional practices.